ANALISIS KINERJA PEGAWAI DIREKTORAT KESEHATAN KERJA DAN OLAHRAGA KEMENTERIAN KESEHATAN JAKARTA SELATAN TAHUN 2021. - Endah Rahayu Ningrum; Sari Ningsih (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
Performance in government administration is the main responsibility of a leader. An employee who is required to do the task well and as much as possible will affect good work results. But sometimes an employee does his job beyond the working hours. In fact, there are often consequences if you don't complete the job. Work hours that are busy and outside the working hour limit result in fatigue. The purpose of this research is to find out how the performance of employees, the inhibiting factors for the decline in employee performance, and to find out the solutions made by the Directorate of Occupational Health and Sports, Ministry of Health, South Jakarta. This type of research is descriptive qualitative. This study uses the theory of Bernadin and Russell, namely: Quality, Quantity, Timeliness, Cos Effectiveness, Need for Supervision, Interpersonal Impact. The result of this research is that the employee's performance is quite good in terms of quality, quantity, cost effectiveness and need for supervision. The inhibiting factor is that employees cannot manage time for their work so that there are employees who are overtime. Key performance indicators are tools to measure employee performance or performance. The existence of a key performance indicator explaining the performance performance that the Ministry of Health is trying to achieve. With the key performance indicators, employees can do their work according to the objectives of the Ministry of Health and the Directorate of Occupational Health and Sports. According to the key performance indicators, Bernadin and Russell's theory can be applied